Pokémon GO: Mobile media play, place-making, and the digital wayfarer. (January 2017) - Hjorth, Larissa; Richardson, Ingrid
This special commentary for Mobile Media & Communication seeks to put these divisive debates in context. Through the lens of Pokémon GO, we can understand and critically interpret a variety of issues involved in the politics and practice of playful mobile media. These issues move across debates around location-aware technologies in constructions of privacy (Coldewey, 2016; Cunningham, 2016), risk and surveillance (Machkovech, 2016; Mishra, 2016) to the role of mobile media in commodifying (Evangelho, 2016) and expanding the social, cultural, and creative dimensions of play (Isbister, 2016; Mäyrä, 2012). As the mobile media and game theorists in this commentary highlight, the game sits at the nexus of several technological and cultural trajectories: the playful turn; the ubiquity of location-based and haptic mobile media (and apps and games); innovative game design; the effects of digital mapping technologies; the intertwining of performative media games and art; our individual and collective memories of playworlds and transmedia universes; the increasing importance of issues concerning privacy and risk in public spaces; the ongoing augmentation of place and space; and the politics embedded in this hybrid experience of the lifeworld.